A matrix approach to the binomial theorem - Stanimirovic, S. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Motivated by the formula x^n = _k=0^n(n k) (x - 1)^k we investigate factorizations of the lower triangular Toeplitz matrix with (i, j)th entry equal to x^i-j via the Pascal matrix. In this way, a new computational approach to a generalization of the binomial theorem is introduced. Numerous combinatorial identities are obtained from these matrix relations.